2015
DOI: 10.15252/emmm.201404134
|View full text |Cite
|
Sign up to set email alerts
|

Navigator‐3, a modulator of cell migration, may act as a suppressor of breast cancer progression

Abstract: Dissemination of primary tumor cells depends on migratory and invasive attributes. Here, we identify Navigator-3 (NAV3), a gene frequently mutated or deleted in human tumors, as a regulator of epithelial migration and invasion. Following induction by growth factors, NAV3 localizes to the plus ends of microtubules and enhances their polarized growth. Accordingly, NAV3 depletion trimmed microtubule growth, prolonged growth factor signaling, prevented apoptosis and enhanced random cell migration. Mathematical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 59 publications
8
41
0
Order By: Relevance
“…With regard to the NAV-3 in HCC, there has been paucity of data till now. In our study, our results showed that knock-down of NAV-3 can promote both the proliferation and migration of HCC cells, which was in agreement with findings by Cohen-Dvashi H and colleagues [11] in breast cancer. In HCC tissues, we found that lower expression of NAV-3 was significantly associated with poor prognosis, which was also consistent with conclusions given by Carlsson E et al [15] in nervous system tumors and Cohen-Dvashi H et al [11] in breast cancer that NAV-3 may be a potential new prognostic biomarker, despite the limited cases of HCC we've employed and enrolled.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…With regard to the NAV-3 in HCC, there has been paucity of data till now. In our study, our results showed that knock-down of NAV-3 can promote both the proliferation and migration of HCC cells, which was in agreement with findings by Cohen-Dvashi H and colleagues [11] in breast cancer. In HCC tissues, we found that lower expression of NAV-3 was significantly associated with poor prognosis, which was also consistent with conclusions given by Carlsson E et al [15] in nervous system tumors and Cohen-Dvashi H et al [11] in breast cancer that NAV-3 may be a potential new prognostic biomarker, despite the limited cases of HCC we've employed and enrolled.…”
Section: Discussionsupporting
confidence: 93%
“…No more study mentioned any miRNA that could potentially regulate NAV-3 in diseases in any form. Consequently, based on the previous studies in cancers [10,11,15], it fairly can be suggested that NAV-3 may play an anti-oncogenic role in cancers, which was backed up by our current study in HCC.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 72%
See 2 more Smart Citations
“…The loss of chromosome 12q21.2 encompasses NAV3, whose silencing was recently reported to inhibit apoptosis of breast cancer cells (Cohen-Dvashi et al 2015). USP-13-Med cells also seem to have dysfunctional p53 signaling.…”
Section: Discussionmentioning
confidence: 95%